Novel thermophilic genera Geochorda gen. nov. and Carboxydochorda gen. nov. from the deep terrestrial subsurface reveal the ecophysiological diversity in the class Limnochordia - Karnachuk, Olga V.; Lukina, Anastasia P.; Avakyan, Marat R.; Kadnikov, Vitaly V.; Begmatov, Shahjahon; Beletsky, Alexey V.; Vlasova, Ksenia G.; Novikov, Andrei A.; Shcherbakova, Viktoria A.; Mardanov, Andrey V.; Ravin, Nikolai V. (Frontiers in Microbiology, 2024)
The class Limnochordia harbors a single cultivated member, the mesophilic Limnochorda pilosa, isolated from a meromictic lake, and despite numerous molecular signatures reported for various ecosystems, the ecophysiological versatility of this deeply branched lineage of Firmicutes (Bacillota) remains poorly understood. The goal of the present study was to use targeted cultivation based on metagenome-assembled genome from a deep terrestrial aquifer in Western Siberia to isolate two new thermophilic members of the class. Isolates described as Geochorda subterranea gen. nov. sp. nov. and Carboxydochorda subterranea gen. nov. sp. nov. within the Geochordaceae fam. nov. were capable of both anaerobic and aerobic respiration with fumarate and O2, respectively, using simple sugars as electron donors. Cultivated Geochordaceae have demonstrated fermentative growth and degradation of polymers including starch, maltose, maltodextrin, xylan, and chitin. Carboxydotrophic C. subterranea sp. nov. exhibited autotrophic growth via the Calvin-Benson-Bassham cycle with CO, H2 and formate as electron donors and O2 as electron acceptor, adding metabolic flexibility to the bacterium in the nutrient-depleted "deep biosphere" and supporting the possibility of aerobic metabolism in the deep subsurface. The broad physiological potential deciphered from physiological experiments and comparative genomic data explains the widespread distribution of uncultivated members of the class Limnochordia in various ecosystems, where they can oxidize complex organic substrates through both, aerobic and anaerobic respiration, as well as pursue a chemolithotrophic lifestyle through oxidation H2 or CO.